Gender mainstreaming in climate mobilities-related governance in Peru - Morales Villalobos, Astrid Carolayn (2023)
The effects of climate change on human beings are increasingly visible, and one of them is mobility. The discipline of climate mobilities is relatively a young one, and the study of gender within this is even more recent. Climate change can, sometimes, exacerbate existing inequalities. In response, experts argue that these vulnerability to climate change can be reduced to the extent that policies are carefully designed and implemented. Peru is a country highly vulnerable to climate change, not only because of its physical characteristics but also because of its socio-economic inequalities. Recent studies have shown the challenges of gender mainstreaming in climate policy and the limited coverage of mobility issues in Peru. Therefore, this study aimed to contribute to greater attention to the gender perspective in the public debate on climate mobilities by analysing the nexus between climate change, human mobilities and gender in the Peruvian context. In this research, the multi-causal nature of mobilities and the incorporation of a gender perspective have been taken into account as part of the framework of analysis. As part of the latter, concepts such as intersectionality, gender equity and empowerment have also been considered. Likewise, in order to achieve the research objective, the analysis of normative documents and semi-structured interviews have been used as qualitative methods. After analysing the findings, it can be said that in the recent construction of the relationship between climate change, human mobilities, and gender in Peru 1) there are difficulties in recognising climate change as one of the causes of mobilities; 2) the gender approach is implemented as a women's issue; and 3) the main relationship between gender and mobility is understood in terms of differentiated impacts and the vulnerability of the migrant population. The results of this research can be a starting point for future analyses of the relationship between climate change, mobilities and gender, as well as for guiding the development and updating of forthcoming policies.